Development of a computer code for the calculation of self-absorption correction factors in γ-spectrometry applications - Alafogiannis, Ioannis; Tugnoli, Francesca; Mitsios, Iason; Anagnostakis, Marios (HNPS Advances in Nuclear Physics, 2022)
In γ-spectroscopy applications, one of the main effects that needs to be considered is the self absorption of the photons – especially of low energy – within the photon source, which may be significantly different between the calibration standard and the sample analyzed. This effect is highly dependent on material composition and density and sample thickness. A common way of dealing with the self-absorption issue is by using Efficiency Correction Factors (ECF), to take into consideration the different absorbing properties between the calibration standard and the sample. This work presents the on-going development of a MATLAB code for ECF calculation. The code calculates ECF for a variety of material matrices and compositions, focusing on Naturally Occurring Radioactive Materials (NORM), which may have high density and contain high Z elements. The results of the code were compared with other methods of ECF calculation, such as Monte-Carlo simulation.